Membrane-free Electrocatalysis of CO2 to C2 on CuO/CeO2 Nanocomposites - Tian, Yangming; Fei, Xiang; Ning, Hui; Wang, Wenhang; Tan, Xiaojie; Wang, Xiaoshan; Ma, Zhengguang; Guo, Zhihao; Wu, Mingbo (Frontiers in Chemistry, 2022)
Carbon dioxide electroreduction (CO2RR) with renewable energy is of great significance to realize carbon neutralization. Traditional electrolysis devices usually need an ion exchange membrane to eliminate the interference of oxygen generated on the anode. Herein, the novel CuO/CeO2 composite was facilely prepared by anchoring small CuO nanoparticles on the surface of CeO2 nanocubes. In addition, CuO(002) crystal planes were induced to grow on CeO2(200), which was preferable for CO2 adsorption and C-C bond formation. As the catalyst in a membrane-free cell for CO2RR, the Cu+ was stabilized due to strong interactions between copper and ceria to resist the reduction of negative potentials and the oxidation of oxygen from the counter electrode. As a result, a high Faradaic efficiency of 62.2% toward C2 products (ethylene and ethanol) was achieved for the first time in the membrane-free conditions. This work may set off a new upsurge to drive the industrial application of CO2RR through membrane-free electrocatalysis.